Influence of Shakarim‘s work „Catechism of Muslims“ on the political and social development of Kazakhs at the beginning of the XX century (Journal of Philosophy Culture and Political Science, 2021)
The work of Shakarim Kudaiberdievich “Catechism of Muslims” is one of the first works written inthe Kazakh language at the beginning of the 20th century, covering the three main doctrines of IslamicSharia – “Akida” (Islamic faith), «Fikh» (Islamic law), «Akhlak» (Islamic morality). The writing of this workcoincided with one of the most difficult periods for the Kazakh people. This was due to the baptismalpolicy of the tsarist government to rule the Kazakh steppes, alienating people from their religion andlanguage. To this can be added the low level of literacy among the Kazakh people. Of course, it was notin vain that the work on Islamic Sharia came out at that time. It is known that the reason for writing thiswork was the political, social, economic and spiritual situation of people at that time. The importance ofstudying our topic is obvious here.The main purpose of the article is to determine the contribution to the development of the Kazakhpeople by studying the reasons for writing the work «Catechism of Muslims». The article examines thehistory and reasons for writing the work of Shakarim Kudaiberdievich «Muslim catechesis». The mostimportant aspects of this work for the Kazakh people are considered. The research included content andthematic analysis of historical data, archives, articles collected on this topic. Decomposition, selection,hermeneutics, descriptive methods were used to achieve the research objectives. This article is importantbecause it leads to the collection of evidence and data from similar research on this topic.Key words: Shakarim, colonialism, politics, religion, Kazakh, development, influence.